Reform of Local Government in France, Always Starts Again - CABANIS André; PĂCEȘILĂ Mihaela (Applied Research in Administrative Sciences)
The policy of reforming municipalities in the French state shows continuity as regards its objectives while pointing out instability as regards the achievements. The paper aims to analyse the policy of local government reform in France, highlighting the challenges of reducing fragmentation of France’s territory and the distribution of powers between the various constituencies: municipalities, departments, and regions. The data collection method used in this paper included the document analysis considered by the authors to be the best way to conduct a research on this topic. The analysis indicates that the local leaders are not able to take the necessary measures to ensure the progress of the reform, on one hand, and they fail to reach a consensus as regards the administrative-territorial division and the simplification of local election procedures and division of competencies between three tiers, on the other hand.